1999
DOI: 10.1086/314598
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Activation in Muscle Biopsy Samples Is Related to Clinical Severity in Human Cerebral Malaria

Abstract: To test the hypothesis of vascular sequestration of parasitized erythrocytes in Plasmodium falciparum malaria in vivo, a pathologic and immunohistochemical study was done of the microvasculature of skeletal muscle biopsy samples from P. falciparum malaria patients at different stages of severity. Parasitized red blood cells sequestered in the skeletal muscle vessels were observed in samples from necropsies but were never demonstrated in biopsy specimens. Vascular cell adhesion molecule-1 and E-selectin express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
(25 reference statements)
1
15
0
2
Order By: Relevance
“…Widespread up-regulation of adhesion receptors ICAM-1 and E-selectin in cerebral vessels has supported the view of endothelial activation in fatal malaria [16], as well as a subsequent study that demonstrated a positive correlation between disease severity and induction of TNF, ICAM-1, VCAM-1, E-selectin and P-selectin in muscle biopsies, indicating widespread systemic EC activation [46].…”
Section: Direct Activation Of Ecsmentioning
confidence: 85%
“…Widespread up-regulation of adhesion receptors ICAM-1 and E-selectin in cerebral vessels has supported the view of endothelial activation in fatal malaria [16], as well as a subsequent study that demonstrated a positive correlation between disease severity and induction of TNF, ICAM-1, VCAM-1, E-selectin and P-selectin in muscle biopsies, indicating widespread systemic EC activation [46].…”
Section: Direct Activation Of Ecsmentioning
confidence: 85%
“…Because it is not possible to access brain endothelium in life, to demonstrate the relevance of this IE-associated endothelial pathology in vivo, a surrogate tissue was required. Previous severe malaria studies have employed immunostaining on dermal 38 or muscle 39 biopsies, but these tissues lacked either endothelial activation 38 or IE sequestration 39 even in severe disease. We used subcutaneous biopsies, which exhibited both endothelial activation and IE sequestration, to demonstrate that EPCR and TM are reduced in CM in vivo.…”
Section: Blood 1 August 2013 X Volume 122 Number 5 Loss Of Protein mentioning
confidence: 99%
“…The injured skeletal muscles has biomarkers relating with severity of falciparum malaria infection [16, 21, 22], and the sequestration of infected red blood cells has been pointed out as the cause for these processes. Pronounced deviation in normal serum levels of creatine kinase (CK) have been also reported in malaria patients, affecting skeletal muscles [16, 21].…”
Section: Malaria Affecting Skeletal Musclesmentioning
confidence: 99%